Ego Defense Mechanisms in the Main Character Nawai in the Novel Rumah Lebah by Ruwi Meita: Mekanisme Pertahanan Ego pada Tokoh Utama Nawai dalam Novel Rumah Lebah Karya Ruwi Meita - Dina Widya Lestari; U’um Qomariyah (Anthology: Journal of Language, Literature, and Learning, 2025)
Novels as one of the literary works that represent social and psychological problems become more interesting and diverse to study. The main character "Nawai" in the novel Rumah Lebah by Ruwi Meita represents human psychological phenomena, especially in relation to ego defense mechanisms. This novel presents the complex inner dynamics of the character Nawai, making it interesting to study through Sigmund Freud's psychoanalytic approach. Specifically, this study aims to identify and describe the forms of ego defense mechanisms of the main character based on Freud's theory. The method used is descriptive qualitative with content analysis techniques. The main data sources in this study are quotations in the novel that show the psychological aspects of the character Nawai. After the data was collected, the data was analyzed in depth and interpretatively. Based on the study that has been done, there are several types of ego defense that can be identified, such as repression, denial, sublimation, diversion, rationalization, regression, and projection carried out by the main character Nawai. This leads to the possibility of multiple personality disorder (DID) in Nawai. In this novel, it is described how mental disorders can affect behavior, such as behavioral instability, emotional dependence, and difficulty identifying identity. This novel describes in depth how trauma and emotional stress can form psychological disorders that affect a person's behavior and personality. This research is expected to contribute to the study of literature combined with psychology, and can provide a deeper understanding to the wider community about the importance of caring about mental health. Novel sebagai salah satu karya sastra yang merepresentasikan berbagai masalah kehidupan seperti masalah sosial dan psikologi amat menarik untuk dikaji. Salah satu novel yang ditulis oleh Ruwi Meita, yaitu Rumah Lebah merupakan novel bergenre psychological thriller. Novel ini menyuguhkan dinamika batin tokoh Nawai yang kompleks, sehingga menarik untuk dikaji melalui pendekatan psikoanalisis Sigmund Freud. Secara spesifik, penelitian ini bertujuan untuk mengidentifikasi dan mendeskripsikan bentuk-bentuk mekanisme pertahanan ego tokoh utama berdasarkan teori Freud. Metode yang digunakan adalah deskriptif kualitatif dengan teknik analisis isi. Sumber data utama dalam penelitian ini adalah kutipan-kutipan dalam novel yang menunjukkan aspek psikologis tokoh Nawai. Setelah data dikumpulkan, data dianalisis secara mendalam. Berdasarkan kajian yang telah dilakukan, Terdapat beberapa jenis pemertahanan ego yang dapat diidentifikasi, seperti represi, penyangkalan, sublimasi, pengalihan, rasionalisasi, regresi, dan proyeksi yang dilakukan oleh tokoh utama Nawai. Hal ini mengarah pada kemungkinan gangguan kepribadian ganda (DID) pada Nawai. Dalam Novel ini, digambarkan bagaimana gangguan mental dapat mempengaruhi perilaku, seperti ketidakstabilan perilaku, ketergantungan emosional, dan kesulitan mengidentifikasi identitas. Novel ini menggambarkan secara mendalam bagaimana trauma dan tekanan emosional dapat membentuk gangguan psikologis yang mempengaruhi perilaku dan kepribadian seseorang. Penelitian ini diharapkan dapat memberikan kontribusi pada kajian sastra yang digabungkan dengan psikologis, serta dapat memberikan pemahaman yang lebih mendalam kepada masyarakat luas tentang pentingnya peduli dengan kesehatan mental.